Recent Advances in Metal, Ceramic, and Metal-Ceramic Composite Films/Coatings (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This reprint gathers works on various coating materials and technologies aimed at the improvement of materials’ properties, such as corrosion resistance or biocompatibility. Systematic studies demonstrate how the structure and morphology of coatings can change the mechanical, chemical and various functional properties of materials. The reprint contributes to the better understanding of various phenomena induced by metal, ceramic or composite coatings in core materials and, thus, it can help in the more rational design of the selected material’s properties in future studies by the application of coatings.